relationship between organizational culture and competencies - Correia, Anabela Gomes; Fernández, Luis González (Conferência - Investigação e Intervenção em Recursos Humanos, 2014)
This study presents a model, which analyses possible relationships between the perception of organizational culture and competence. Organizational culture was defined in accordance with the four cultural guidelines, which correspond to the subscales defined by the FOCUS questionnaire: support, rules, innovation and goal orientation. Competences were defined along two dimensions: technical and generic. The organizations, which participated in the study, principally in the public sector, tended to present a Rule-oriented culture, distant from Innovation. In terms of competences there existed a general tendency within the organizations, especially the public sector, to place higher value upon technical competences. A relationship was found between culture and competences. Hence, Goal orientation was associated with technical competences and an Innovation cultural orientation was associated with generic competences. We concluded that the organizations, which participated in this study, particularly from the public sector, show poor openness to the exterior, adaptability and flexibility. Furthermore there is little stimulation or incentive for initiative or autonomy.